Prosedur Berperkara: Mekanisme Penyelesaian Sengketa pada Badan Arbitrase Syariah Nasional - Dinda Fasyya; Mujnah Fitria; Nadhifa Kharida Nissa (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This  research examines the procedural mechanism for dispute resolution at the National Sharia Arbitration Board (BASYARNAS) as an alternative to litigation in resolving sharia-based disputes. The study aims to analyze the stages of proceedings, legal foundations, and effectiveness of arbitration procedures applied by BASYARNAS. This research employs a normative juridical method with a statutory and conceptual approach, utilizing primary legal materials such as laws and regulations related to arbitration and sharia economic disputes, as well as secondary legal materials in the form of books, journals, and legal literature. The results show that the dispute resolution mechanism at BASYARNAS is conducted through structured stages, including submission of arbitration claims, examination of disputes, and issuance of arbitration awards that are final and binding. The procedure emphasizes principles of justice, legal certainty, efficiency, and compliance with Islamic law. BASYARNAS plays a significant role in providing an effective dispute resolution forum for sharia economic actors; however, challenges remain in the implementation and execution of arbitration awards, particularly regarding public awareness and institutional support.